Lignin-containing nanocellulose based on camellia oleifera fruit cattail as well as preparation method and application of lignin-containing nanocellulose

Nanocellulose was extracted from Camellia oleifera fruit by DES pretreatment and organic weak acid hydrolysis, which solved the problems of low resource utilization and environmental pollution of Camellia oleifera fruit and prepared a highly efficient nanocellulose material that can be applied in multiple fields.

CN121248964APending Publication Date: 2026-01-02HUNAN ACAD OF FORESTRY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511412974.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-29
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

Existing technologies are difficult to utilize camellia oleifera fruit resources efficiently, the preparation process is not environmentally friendly, and it is difficult to achieve industrial production of lignin-containing nanocellulose.

Method used

Nanocellulose was extracted from Camellia oleifera fruit by using DES pretreatment combined with organic weak acid hydrolysis. High-crystallinity LCNF was prepared by controlling the hydrolysis conditions, thereby changing its size and morphology.

Benefits of technology

This method enables the high-value utilization of Camellia oleifera fruit and cattail, reduces environmental impact, and produces nanocellulose with high specific surface area and good biocompatibility, which can be widely used in optoelectronics, biomedicine and food industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121248964A_ABST
    Figure CN121248964A_ABST
Patent Text Reader

Abstract

The invention discloses lignin-containing nanocellulose based on camellia oleifera fruit and cattail as well as a preparation method and application thereof, and relates to the technical field of production of biomass nanomaterials, the lignin-containing nanocellulose based on camellia oleifera fruit and cattail comprises the following components in percentage by mass: 8%-15% of lignin, 3%-8% of hemicellulose and 70%-90% of cellulose; the preparation method of the lignin-containing nanocellulose comprises the following steps: S1, treating oil tea fruit cattail; s2, performing DES pretreatment on the Camellia oleifera fruit powder; s3, performing acidolysis and centrifugation on the fruit peel cellulose to obtain lignin-containing nano cellulose; s4, dialyzing the nano cellulose containing the lignin; the lignin-containing nanocellulose is used for preparing the LCNF / PVA composite film, and the LCNF / PVA composite film can be used as a food preservative film; the lignin-containing nanocellulose prepared by the preparation method disclosed by the invention has high specific surface area, high surface chemical activity and good biocompatibility and degradability, and is widely applied to the field of food industry.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of biomass nanomaterial production, in particular to a lignin-containing nanocellulose based on oil tea fruit pomace and a preparation method and application thereof. BACKGROUND

[0002] Oil tea (Camellia oleifera) is a unique woody oil crop in China, and is known as one of the world's four major woody edible oil trees along with oil palm, olive, and coconut. With the vigorous development of oil tea planting in China, the current oil tea planting area has reached 4.5333 million hectares, accounting for more than 95% of global oil tea resources. However, a large amount of by-products are produced during the processing of oil tea, with oil tea fruit pomace being one of the main by-products, accounting for 50-60% of the oil tea fruit. At present, a small part of oil tea fruit pomace is used to prepare activated carbon and organic fertilizer, while the vast majority is directly discarded or burned, with a very low development and utilization rate, resulting in a great waste of oil tea fruit pomace resources.

[0003] In recent years, analysis of the fiber three-element content of oil tea fruit pomace shows that cellulose accounts for only 14-20%, while lignin and hemicellulose account for 30-36% and 24-32%, respectively. The lignin content is relatively high, while the cellulose content is relatively low, so there are few studies on the preparation of nanocellulose using oil tea fruit pomace as the raw material. Lignin-containing nanocellulose fiber (LCNF) has the advantages of high yield, low cost, and little environmental impact, and is a promising bio-based material. The lignin retained in LCNF helps to improve hydrophobicity, reduce polarity, and enhance thermal stability.

[0004] Currently, LCNF is mainly separated from natural cellulose through a top-down method, including chemical hydrolysis, mechanical dispersion, and enzymatic hydrolysis. These processing methods are usually time-consuming, and face the problems of environmental unfriendliness and difficulty in industrialization. In addition, the control of lignin content and aspect ratio is a key issue in the preparation of LCNF. Therefore, in order to solve the above problems, the present application provides a lignin-containing nanocellulose based on oil tea fruit pomace and a preparation method and application thereof. SUMMARY

[0005] In view of the above, the present application aims at the defects in the prior art, and the main purpose is to provide a lignin-containing nanocellulose based on camellia oleifera fruit peel and a preparation method and application thereof, which uses camellia oleifera fruit peel as a raw material and adopts DES pretreatment, thereby realizing high-value utilization of camellia oleifera fruit peel and reducing damage to the environment; the lignin-containing nanocellulose prepared by the preparation method of the lignin-containing nanocellulose based on camellia oleifera fruit peel has high specific surface area, high surface chemical activity, good biocompatibility and degradability, and can be widely applied to the fields of photoelectricity, biomedicine and food industry.

[0006] To achieve the above-mentioned purpose, the present application adopts the following technical solutions: A lignin-containing nanocellulose based on camellia oleifera fruit peel, comprising the following components in percentage by mass: lignin (8%-15%), hemicellulose (3%-8%) and cellulose (70%-90%).

[0007] As a preferred solution, the lignin-containing nanocellulose based on camellia oleifera fruit peel comprises the following components in percentage by mass: lignin 10.6%, hemicellulose 5.2% and cellulose 83.8%; the lignin-containing nanocellulose, i.e. LCNF, has a length of 200-2400 nm, an aspect ratio of 20-80, a crystallinity of 80-85%, and the average particle size of the lignin particles is 100-500 nm.

[0008] A preparation method of a lignin-containing nanocellulose based on camellia oleifera fruit peel, comprising the following steps: S1, mechanically treating camellia oleifera fruit peel to obtain camellia oleifera fruit peel powder;

[0009] S2, pretreating the camellia oleifera fruit peel powder by DES to obtain lignin-containing fruit peel cellulose;

[0010] S3, performing organic weak acid hydrolysis and centrifugation on the lignin-containing fruit peel cellulose to obtain lignin-containing nanocellulose;

[0011] S4, dialyzing the lignin-containing nanocellulose to neutral.

[0012] As a preferred solution, the pretreatment of the camellia oleifera fruit peel powder by DES in step S2 specifically comprises: preparing a DES solvent by mixing and heating a hydrogen bond acceptor and a hydrogen bond donor, the hydrogen bond acceptor is choline chloride, and formic acid, acetic acid, lactic acid, maleic acid and oxalic acid are used as the hydrogen bond donors respectively; the molar ratio of the hydrogen bond acceptor and the hydrogen bond donor is 0.3-3; the camellia oleifera fruit peel powder is added into the DES solvent for reaction to obtain the lignin-containing fruit peel cellulose.

[0013] As a preferred solution: the step S2 is that the camellia fruit peel powder is added into the DES solvent to react under the condition of 60-120 ℃ for 2-15 h; the reaction is terminated by adding anhydrous ethanol, and the camellia fruit peel cellulose containing lignin is obtained by filtering with ethanol until neutral; the molar ratio of the hydrogen bond acceptor and the hydrogen bond donor is 0.5-2, and the solid-liquid ratio of the camellia fruit peel powder and the DES is 1 g:(10-20) mL.

[0014] As a preferred solution: the step S3 is that the camellia fruit peel cellulose containing lignin is dispersed in an organic weak acid solution, and then the reaction is terminated by adding 10-15 times of volume of 3-5 ℃ pre-cooled deionized water after oil bath stirring at 60-120 ℃ for 2-10 h, and the acid solution and the precipitate are collected by centrifugal washing several times, wherein the acid solution is used for subsequent recycling, and the precipitate is the camellia fruit peel cellulose containing lignin.

[0015] As a preferred solution: the organic weak acid in the step S3 is one of maleic acid, citric acid and oxalic acid, the solid-liquid ratio of the camellia fruit peel cellulose containing lignin and the organic weak acid solution is 1 g:(10-80) mL, and the concentration of the organic weak acid is 0.1-1 mol / L; the recycling of the acid solution is that the acid solution is rotary evaporated at 60-100 ℃ for 0.5-2 h, and the organic weak acid obtained by rotary evaporation is collected.

[0016] As a preferred solution: the step S1 is that the dried camellia fruit peel is crushed and passed through a 60-120 mesh sieve to obtain the camellia fruit peel powder; and the step S4 is that the camellia fruit peel cellulose containing lignin is placed in a dialysis bag with a molecular weight cut-off of 8000-14000 Da, and then dialyzed in distilled water until neutral.

[0017] An application of camellia fruit peel-based lignin-containing nanocellulose, the lignin-containing nanocellulose is used for preparing an LCNF / PVA composite film, the PVA is polyethylene glycol; and the LCNF / PVA composite film can be used as a food preservative film.

[0018] As a preferred solution: the step of preparing the LCNF / PVA composite film by the lignin-containing nanocellulose is: mixing 0.5-2% lignin-containing nanocellulose water dispersion, i.e. LCNF water dispersion, with 5-10% PVA aqueous solution; the volume ratio of the LCNF water dispersion to the PVA aqueous solution is 0.2-2:1; heating and stirring at 60-120℃ for 10-50min, mixing by ultrasonic and pouring into a mold, drying at 50-90℃ for 12h to obtain the LCNF / PVA composite film; the thickness of the LCNF / PVA composite film is 10-50μm, and the contact angle is 65-79.69°.

[0019] Compared with the prior art, the present application has obvious advantages and beneficial effects, specifically, from the above technical solution, it can be known that:

[0020] Firstly, the present application uses camellia fruit peel as a raw material and adopts DES pretreatment, thereby realizing high-value utilization of camellia fruit peel and reducing damage to the environment.

[0021] Secondly, the present application adopts an organic weak acid hydrolysis method, which can realize high utilization value of the organic weak acid through recovery of the organic weak acid, and can prepare LCNF with high crystallinity and change the size and morphology thereof by controlling the hydrolysis conditions. The prepared lignin-containing nanocellulose has high specific surface area, high surface chemical activity, good biocompatibility and degradability, and can be widely applied in the fields of photoelectricity, biomedicine and food industry.

[0022] To make the structure characteristics and effects of the present application clearer, specific embodiments will be described in detail below with reference to the drawings. BRIEF DESCRIPTION OF DRAWINGS

[0023] Figure 1 The scanning electron microscope image of the raw material camellia fruit peel and the lignin-containing camellia fruit peel cellulose after DES pretreatment in Example 1 of the present application;

[0024] Figure 2 The scanning electron microscope image of the lignin-containing nanocellulose fiber (LCNF) based on camellia fruit peel obtained in Example 1 of the present application;

[0025] Figure 3 The scanning electron microscope image of the lignin-containing nanocellulose fiber (LCNF) based on camellia fruit peel obtained in Example 2 of the present application;

[0026] Figure 4 The scanning electron microscope image of the lignin-containing nanocellulose fiber (LCNF) based on camellia fruit peel obtained in Example 3 of the present application;

[0027] Figure 5 A macrograph of the LCNF / PVA composite film obtained in Example 4 of the present application was taken 5 cm above the N95 mask;

[0028] Figure 6 A schematic diagram of the contact angle of the LCNF / PVA composite film obtained in Example 4 of the present application. DETAILED DESCRIPTION

[0029] The present application as Figure 1 As shown in FIG. 6, a lignin-containing nanocellulose based on oil tea fruit pulp includes the following components by mass percentage: lignin (8%-15%), hemicellulose (3%-8%), and cellulose (70%-90%).

[0030] The lignin-containing nanocellulose based on oil tea fruit pulp includes the following components by mass percentage: lignin 10.6%, hemicellulose 5.2%, and cellulose 83.8%; the lignin-containing nanocellulose, i.e., LCNF, has a length of 200-2400 nm, an aspect ratio of 20-80, a crystallinity of 80-85%, and an average particle size of lignin particles of 100-500 nm.

[0031] A preparation method of a lignin-containing nanocellulose based on oil tea fruit pulp includes the following steps: S1, mechanically treating oil tea fruit pulp to obtain oil tea fruit pulp powder;

[0032] S2, pretreating the oil tea fruit pulp powder by DES to obtain lignin-containing fruit pulp cellulose;

[0033] S3, performing organic weak acid hydrolysis and centrifugation on the lignin-containing fruit pulp cellulose to obtain lignin-containing nanocellulose;

[0034] S4, dialyzing the lignin-containing nanocellulose to neutral.

[0035] In this step S2, the DES pretreatment of the oil tea fruit pulp powder is specifically as follows: a DES solvent is prepared by mixing and heating a hydrogen bond acceptor and a hydrogen bond donor; the hydrogen bond acceptor is choline chloride, and formic acid, acetic acid, lactic acid, maleic acid, and oxalic acid are used as the hydrogen bond donors; the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 0.3-3; the oil tea fruit pulp powder is added to the DES solvent for reaction to obtain the lignin-containing fruit pulp cellulose.

[0036] The conditions for adding the oil tea fruit pomace powder to the DES solvent for reaction in this step S2 are: reacting at 60-120°C for 2-15 h; adding anhydrous ethanol to terminate the reaction, and extracting with ethanol until neutral to obtain lignin-containing fruit pomace cellulose; the molar ratio of hydrogen bond acceptor to hydrogen bond donor is 0.5-2, and the solid-liquid ratio of oil tea fruit pomace powder to DES is 1 g:(10-20) mL.

[0037] This step S3 specifically comprises: dispersing the lignin-containing fruit pomace cellulose in an organic weak acid solution, stirring in an oil bath at 60-120°C for 2-10 h, then adding 10-15 times the volume of 3-5°C pre-cooled deionized water to terminate the reaction, and centrifuging and washing several times to collect the supernatant acid and the precipitate, respectively, wherein the supernatant acid is used for subsequent recycling, and the precipitate is lignin-containing nanocellulose.

[0038] The organic weak acid in this step S3 is one of maleic acid, citric acid and oxalic acid, the solid-liquid ratio of lignin-containing fruit pomace cellulose to organic weak acid solution is 1 g:(10-80) mL, and the concentration of the organic weak acid is 0.1-1 mol / L; the supernatant acid is recovered by rotary evaporation of the supernatant acid at 60-100°C for 0.5-2 h to collect the organic weak acid obtained by rotary evaporation.

[0039] This step S1 specifically comprises: crushing and sieving dried oil tea fruit pomace through a 60-120 mesh sieve to obtain oil tea fruit pomace powder; and step S4 specifically comprises: placing the lignin-containing nanocellulose in a dialysis bag with a molecular weight cut-off of 8000-14000 Da; and dialyzing in distilled water until neutral.

[0040] An application of lignin-containing nanocellulose based on oil tea fruit pomace, the lignin-containing nanocellulose is used to prepare an LCNF / PVA composite film, and the LCNF / PVA composite film can be used as a food preservative film.

[0041] The steps for preparing the LCNF / PVA composite film from the lignin-containing nanocellulose are: mixing 0.5-2% lignin-containing nanocellulose water dispersion, i.e. LCNF water dispersion, with 5-10% PVA aqueous solution;

[0042] The volume ratio of the LCNF water dispersion to the PVA aqueous solution is 0.2-2:1; heating and stirring at 60-120°C for 10-50 min, pouring into a mold by ultrasonic mixing, and drying at 50-90°C for 12 h to obtain the LCNF / PVA composite film; the thickness of the LCNF / PVA composite film is 10-50μm, and the contact angle is 65-79.69°.

[0043] The method for removing lignin from biomass raw materials in the prior art is most common in alkali treatment. The method mainly removes part of lignin and hemicellulose by destroying the ester bond connecting the components in lignocellulose and eliminating the acetyl group and furfuryl acid group in hemicellulose. The method is widely used because of its good lignin and hemicellulose removal effect and low cost, but the method produces a large amount of high-alkalinity wastewater that needs to be treated, and the by-product reaction generates difficult-to-degrade phenolic pollutants, significantly increasing environmental protection costs and resource loss.

[0044] Compared with alkali treatment, organic solvent and ionic liquid treatment have mild reaction conditions, are environmentally friendly and can be recycled. Organic solvents mainly remove lignin through the similar phase solubility principle, while the super polarity and basic hydrogen bond anion in ionic liquids can break the hydrogen bond to expose the cellulose. However, the synthesis process is complex, has certain toxicity and is relatively high in price, and therefore cannot be widely applied.

[0045] The common methods for preparing LCNF in the prior art include acid hydrolysis, TEMPO oxidation and enzymatic hydrolysis. The acid hydrolysis and TEMPO oxidation often need the participation of various chemical reagents and will produce toxic wastewater, which is a great threat to the environment. Although the enzymatic hydrolysis is the most environmentally friendly and complies with the essence of green chemistry, the high cost limits its application.

[0046] The preparation method of lignin-containing nanocellulose based on oil tea fruit pomace provided by the present application has the following beneficial effects relative to the preparation method in the prior art: the present application uses oil tea fruit pomace as a raw material and adopts DES pretreatment, which not only realizes high-value utilization of oil tea fruit pomace but also reduces damage to the environment; the present application adopts an organic weak acid hydrolysis method, which can not only realize high utilization value of the organic weak acid by recycling the organic weak acid and reduce the cost but also prepare LCNF with high crystallinity and change the size and morphology of the LCNF by controlling the hydrolysis conditions. The prepared lignin-containing nanocellulose has high specific surface area, high surface chemical activity, good biocompatibility and degradability, can be widely applied in the fields of optoelectronics, biomedicine and food industry, and has a wider application range relative to the prior art. The preparation method of lignin-containing nanocellulose based on oil tea fruit pomace provided by the present application has a wider application prospect relative to the prior art.

[0047] Example 1:

[0048] S1, mechanical treatment: dry oil tea fruit pomace is crushed and passed through an 80-mesh sieve to obtain oil tea fruit pomace powder;

[0049] S2, DES pretreatment: prepare DES solvent by mixing choline chloride as hydrogen bond acceptor (HBA) and formic acid as hydrogen bond donor (HBD) with a molar ratio of 1:2, stirring and heating at 90°C for 0.5h. Take an appropriate amount of oil-tea camellia fruit pulp powder obtained in step S1 and add it to the DES with a certain solid-liquid ratio. React at 100°C for 6h, add 200mL of anhydrous ethanol to terminate the reaction, and filter with ethanol until it is neutral to obtain lignin-containing fruit pulp cellulose;

[0050] S3, organic weak acid hydrolysis and centrifugation: disperse the obtained lignin-containing fruit pulp cellulose in an 80% maleic acid solution with a solid-liquid ratio of 1:20, stir and react in an oil bath at 100°C for 4h, then add 10 times the volume of 4°C pre-cooled deionized water to terminate the reaction, and wash several times by centrifugation. Collect the supernatant acid and the precipitate, respectively. The supernatant acid is used for subsequent recycling, and the precipitate is LCNF;

[0051] S4, dialysis of LCNF: load the obtained oil-tea camellia fruit pulp LCNF into a dialysis bag with a molecular weight cut-off of 8000-14000Da, dialyze with deionized water until the pH of the suspension is neutral, then perform ultrasonic dispersion treatment in an ice bath. The ultrasonic power is 100w, the ultrasonic time is 4min, the working time and interval time are 8s and 4s respectively, to obtain an oil-tea camellia fruit pulp LCNF aqueous solution.

[0052] The scanning electron micrographs of the oil-tea camellia fruit pulp as obtained in Example 1 and after DES pretreatment are shown in Figure 1. In Figure 1, A is the scanning electron micrograph of the raw material oil-tea camellia fruit pulp of Example 1, and B is the scanning electron micrograph of the lignin-containing oil-tea camellia fruit pulp cellulose after DES pretreatment in Example 1. As can be seen from Figure 1, the oil-tea camellia fruit pulp after DES pretreatment changes from a structure with a tight structure to a structure with exposed fiber interweaving, indicating that the hemicellulose and lignin have been removed to some extent. In addition, the morphology structure of the LCNF obtained by acidolysis (Figure 2) can be seen to be a nanofiber mixed with nanoparticles, with the size of the nanoparticles being about 150nm, the diameter of the nanofiber being between 15-50nm, and the length being between 800-1600nm.

[0053] Table 1: Content of fiber trichomes in oil-tea camellia fruit pulp and each sample after treatment in Example 1

[0054] Example 2:

[0055] S1, mechanical treatment: crush and pass the dried oil-tea camellia fruit pulp through an 80-mesh sieve to obtain oil-tea camellia fruit pulp powder;

[0056] S2, DES pretreatment: prepare DES solvent by mixing choline chloride as hydrogen bond acceptor (HBA) and lactic acid as hydrogen bond donor (HBD) at a molar ratio of 1:2, stirring and heating at 90°C for 0.5h. Take an appropriate amount of oil tea fruit pulp powder and add it to the DES at a certain solid-liquid ratio. React at 100°C for 6h, add 200mL of anhydrous ethanol to terminate the reaction, and filter with ethanol until neutral to obtain lignin-containing fruit pulp cellulose;

[0057] S3, organic weak acid hydrolysis and centrifugation: disperse the obtained lignin-containing fruit pulp cellulose in an 80% maleic acid solution at a solid-liquid ratio of 1:40, and stir at 100°C in an oil bath for 4h. Then add 10 times the volume of 4°C pre-cooled deionized water to terminate the reaction, and wash several times by centrifugation. Collect the supernatant acid and the precipitate, respectively. The supernatant acid is used for subsequent recycling, and the precipitate is LCNF;

[0058] S4, dialysis of LCNF: load the obtained oil tea fruit pulp LCNF into a dialysis bag with a molecular weight cut-off of 8000-14000Da, dialyze with deionized water until the pH of the suspension is neutral, then perform ultrasonic dispersion treatment in an ice bath. The ultrasonic power is 100w, the ultrasonic time is 4min, the working time and interval time are 8s and 4s respectively, and the oil tea fruit pulp LCNF aqueous solution is obtained.

[0059] Example 2 differs from Example 1 in that the hydrogen bond donor of the green solvent used in step S2 is different, which makes the lignin content of the prepared LCNF different from that of Example 1. The scanning electron microscope image of the oil tea fruit pulp LCNF obtained in Example 2 is shown in Figure 3.

[0060] Example 3:

[0061] S1, mechanical treatment: crush and pass the dried oil tea fruit pulp through an 80-mesh sieve to obtain oil tea fruit pulp powder;

[0062] S2, DES pretreatment: prepare DES solvent by mixing choline chloride as hydrogen bond acceptor (HBA) and formic acid as hydrogen bond donor (HBD) at a molar ratio of 1:2, stirring and heating at 90°C for 0.5h. Take an appropriate amount of oil tea fruit pulp powder and add it to the DES at a certain solid-liquid ratio. React at 100°C for 6h, add 200mL of anhydrous ethanol to terminate the reaction, and filter with ethanol until neutral to obtain lignin-containing fruit pulp cellulose;

[0063] S3, organic weak acid acidolysis and centrifugation: the obtained lignin-containing fruit pulp cellulose was dispersed in an 80% maleic acid solution at a material-to-liquid ratio of 1:60, and after being stirred in an oil bath at 120°C for 4 h, 10 times the volume of 4°C pre-cooled deionized water was added to terminate the reaction, and the supernatant was collected after centrifugal washing several times, and the supernatant was used for subsequent recycling, and the precipitate was LCNF;

[0064] S4, dialysis of LCNF: the obtained LCNF of oil tea fruit pulp was loaded into a dialysis bag with a molecular weight cut-off of 8000-14000 Da, and dialyzed with deionized water until the pH of the suspension was neutral, and then ultrasonic dispersion treatment was performed in an ice bath, the ultrasonic power was 100 w, the ultrasonic time was 4 min, the working time and interval time were 8 s and 4 s respectively, to obtain an oil tea fruit pulp LCNF aqueous solution;

[0065] Recovery of organic weak acid: the supernatant obtained in step S3 was rotary evaporated at 80°C for 2 h, and the organic weak acid obtained by rotary evaporation was collected.

[0066] Example 3 differs from Example 2 in that the hydrogen bond donor of the green solvent used in step S2 is different, and the material-to-liquid ratio in the weak acid acidolysis in step S4 is also different, which makes the aspect ratio of the prepared LCNF and the content of lignin particles different from Example 2, and the scanning electron microscope image of the obtained LCNF is shown in Figure 4.

[0067] Example 4:

[0068] Example 4 is to prepare LCNF / PVA composite membranes by compounding the three kinds of LCNF prepared in Examples 1-3 with PVA.

[0069] Preparation of LCNF / PVA composite membranes: different aspect ratio LCNF obtained in Examples 1-3 was prepared into a composite membrane with 5% PVA at a ratio of 1:5, heated and stirred at 90°C for 30 min, and then ultrasonic dispersion treatment was performed, the ultrasonic power was 100 w, the ultrasonic time was 2 min, the working time and interval time were 8 s and 2 s respectively, to obtain an oil tea fruit pulp LCNF and PVA mixture, pour into a mold, and dry at 75°C for 12 h to obtain an LCNF / PVA composite membrane. And the prepared composite membrane was cut into a 2*1 cm rectangle, and was placed above a N95 mask at a distance of 5 cm for mobile phone shooting to characterize its light transmission; a contact angle measuring instrument was used, 2.0 μL deionized water was added on the membrane to characterize its water contact angle and surface wettability.

[0070] The contact angle measurement chart of the LCNF / PVA composite film obtained in Example 4 is shown in FIG. 5 and FIG. 6, FIG. 5A is a high aspect ratio LCNF / PVA composite film; FIG. 5B is a medium aspect ratio LCNF / PVA composite film; FIG. 5C is a low aspect ratio LCNF / PVA composite film; FIG. 6A is a pure PVA film;

[0071] FIG. 6B is a high aspect ratio LCNF / PVA composite film; FIG. 6C is a medium aspect ratio LCNF / PVA composite film; FIG. 6D is a low aspect ratio LCNF / PVA composite film.

[0072] Example analysis:

[0073] In the present application, Examples 1-3 use oil tea fruit pith as raw material, and after DES treatment, oil tea fruit pith LCNF is obtained, and then organic weak hydrolysis treatment is carried out, followed by centrifugation and ultrasonic dispersion. The yield, length and diameter of the finally prepared oil tea fruit pith LCNF are determined, and the specific determination results are shown in Table 2.

[0074] Table 2: Average length, aspect ratio and crystallinity data of LCNF prepared under different example conditions

[0075] As can be seen from Table 2, the yield of the lignin-containing nanocellulose based on oil tea fruit pith obtained by the preparation method of the present application is 80.01%-85.14%, the average length is 463.48-1077.95 nm, the average diameter is 11.25-13.3 nm, and the aspect ratio is 41.2-81.05. The diameter is in the range of 20 nm. This shows that the prepared LCNF has the characteristics of controllable and adjustable structure and size.

[0076] The LCNF / PVA composite film prepared by compounding the LCNF with different aspect ratios prepared in the present application with PVA has the characteristics of controllable transmittance (FIG. 5) and relatively hydrophobic surface (FIG. 6).

[0077] As can be seen from FIG. 5, the transmittance of the LCNF / PVA composite film with different aspect ratios has obvious difference. The N95 mask seen through the LCNF / PVA composite film with a transmittance aspect ratio of 63 and above is obviously more blurred than the LCNF / PVA composite film with a transmittance aspect ratio of 41. In addition, the contact angle of the prepared LCNF / PVA composite film is all above 69° (FIG. 6) compared with the pure PVA film (contact angle is 37°), which is beneficial to the water resistance of the film material.

[0078] The application has simple production process, is green and environment-friendly, the size and morphology of LCNF can be flexibly controlled by changing the weak acid hydrolysis conditions to meet the needs of different application fields. At the same time, the camellia fruit peel as an agricultural and forestry waste realizes high-value utilization, which has important economic and environmental significance. The lignin-containing nanocellulose can be widely applied in the fields of photoelectricity, biomedicine and food industry due to its excellent physical and chemical properties.

[0079] The application combines green solvent pretreatment and organic weak acid acidolysis to prepare lignin-containing nanocellulose fibers with high aspect ratio, high crystallinity and amphiphilic properties; the obtained lignin-containing nanocellulose is used for preparing food preservative film with good toughness and water resistance; the application not only enriches the raw materials of nanocellulose, effectively solves the environmental pollution and resource waste problems caused by raw materials in the process of camellia fruit peel treatment, and greatly enhances the comprehensive utilization potential of camellia.

[0080] The design emphasis of the application is that: first, the application adopts DES pretreatment with camellia fruit peel as raw material, which realizes high-value utilization of camellia fruit peel and reduces the damage to the environment.

[0081] Second, the application adopts the method of organic weak acid acidolysis, which can realize high utilization value of organic weak acid through recycling organic weak acid, and can prepare LCNF with high crystallinity and change the size and morphology by controlling acidolysis conditions. The obtained lignin-containing nanocellulose has high specific surface area, high surface chemical activity, good biocompatibility and degradability, and can be widely applied in the fields of photoelectricity, biomedicine and food industry.

[0082] The above is only the preferred embodiment of the application, and does not limit the technical scope of the application, so any slight modification, equivalent change and modification made according to the technical essence of the application to the above embodiment are still within the scope of the technical solution of the application.

Claims

1. A lignin-containing nanocellulose based on Camellia oleifera fruit, characterized in that: It comprises the following components by weight percentage: lignin (8%-15%), hemicellulose (3%-8%) and cellulose (70%-90%).

2. The lignin-containing nanocellulose based on Camellia oleifera fruit according to claim 1, characterized in that: The composition by mass percentage includes the following components: 10.6% lignin, 5.2% hemicellulose and 83.8% cellulose; the lignin-containing nanocellulose, i.e., LCNF, has a length of 200-2400 nm, an aspect ratio of 20-80, and a crystallinity of 80-85%, wherein the average particle size of the lignin particles is 100-500 nm.

3. A method for preparing lignin-containing nanocellulose based on Camellia oleifera fruit as described in any one of claims 1-2, characterized in that: The process includes the following steps: S1, mechanically processing the camellia fruit to obtain camellia fruit powder; S2. Camellia oleifera fruit powder was pretreated with DES to obtain lignin-containing fruit cellulose; S3. The lignin-containing fruit cellulose was subjected to organic weak acid hydrolysis and centrifugation to obtain lignin-containing nanocellulose. S4. Dialyze lignin-containing nanocellulose to neutral.

4. The preparation method according to claim 3, characterized in that: In step S2, the DES pretreatment of Camellia oleifera fruit powder specifically involves: preparing a DES solvent by heating a mixture of hydrogen bond acceptors and hydrogen bond donors, with choline chloride as the hydrogen bond acceptor and formic acid, acetic acid, lactic acid, maleic acid, and oxalic acid as hydrogen bond donors, respectively; the molar ratio of the hydrogen bond acceptor to the hydrogen bond donor is 0.3-3; the Camellia oleifera fruit powder is then added to the DES solvent for reaction to obtain lignin-containing fruit cellulose.

5. The preparation method according to claim 4, characterized in that: In step S2, the conditions for adding Camellia oleifera fruit powder to DES solvent for reaction are as follows: reaction at 60-120℃ for 2-15 h; the reaction is terminated by adding anhydrous ethanol, and the mixture is filtered with ethanol until neutral to obtain lignin-containing Camellia oleifera cellulose; the molar ratio of hydrogen bond acceptor to hydrogen bond donor is 0.5-2, and the material-to-liquid ratio of Camellia oleifera fruit powder to DES is 1 g: (10-20) mL.

6. The preparation method according to claim 3, characterized in that: Step S3 specifically involves dispersing lignin-containing fruit cellulose in an organic weak acid solution, stirring in an oil bath at 60-120 ℃ for 2-10 h, then adding 10-15 times the volume of pre-cooled deionized water at 3-5 ℃ to terminate the reaction, and centrifuging and washing several times. The supernatant acid solution and precipitate are collected separately, with the supernatant acid solution used for subsequent recycling and the precipitate being lignin-containing nanocellulose.

7. The preparation method according to claim 6, characterized in that: In step S3, the organic weak acid is one of maleic acid, citric acid, and oxalic acid. The ratio of lignin-containing fruit cellulose to the organic weak acid solution is 1 g: (10-80) mL, and the concentration of the organic weak acid is 0.1-1 mol / L. Recovery of the supernatant acid: The supernatant acid is rotary evaporated at 60-100 ℃ for 0.5-2 h, and the organic weak acid obtained by rotary evaporation is collected.

8. The preparation method according to claim 3, characterized in that: Step S1 specifically involves: pulverizing dried camellia fruit and passing it through a 60-120 mesh sieve to obtain camellia fruit powder; Step S4 specifically involves: placing lignin-containing nanocellulose in a dialysis bag, the molecular weight cutoff of which is 8000-14000 Da; and dialyzing it in distilled water until neutral.

9. An application of a lignin-containing nanocellulose based on Camellia oleifera fruit as described in any one of claims 1-2, characterized in that: The lignin-containing nanocellulose is used to prepare an LCNF / PVA composite film, which can be used as a food preservation film.

10. The application according to claim 9, characterized in that: The steps for preparing the LCNF / PVA composite membrane from lignin-containing nanocellulose are as follows: 0.5-2% of an aqueous dispersion of lignin-containing nanocellulose, i.e., LCNF aqueous dispersion, is mixed with 5-10% of a PVA aqueous solution; the volume ratio of the LCNF aqueous dispersion to the PVA aqueous solution is 0.2-2:1; the mixture is heated and stirred at 60-120 ℃ for 10-50 min, ultrasonically mixed, poured into a mold, and dried at 50-90 ℃ for 12 h to obtain the LCNF / PVA composite membrane; the thickness of the LCNF / PVA composite membrane is 10-50 μm, and the contact angle is 65-79.69°.

Citation Information

Cited By

  • High-light-transmittance low-haze bamboo holocellulose film and preparation method thereof

    CN121930519A